EXAMINING THE IMPACT OF MARKET RISK PREMIUM, COMPANY SCALE, AND BOOK-TO-MARKET RATIO ON STOCK RETURNS: A COMPREHENSIVE STUDY OF IDX LISTED SOE COMPANIES IN 2021 - Solihah, Rika Siti Jakiatus; Pramesti, Muthia (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2024)
This research explores Fama and French's Three Factor Model (1992), which identified key determinants of corporate returns. Using factors such as rate of return of risky investment, company size, and a comparison between book and market value, the research tested the model in the Indonesian context, using companies listed on the Indonesia Stock Exchange in the year 2021. The investigation focuses specifically on state-owned enterprises (SOE) which have a strategic role in economic recovery. Employing a panel data regression analysis, the study utilizes daily closing stock prices from six portfolios, each comprising stocks from 31 state-owned enterprises. The empirical findings indicate that, individually and collectively, all three factors—market risk premium, firm size, and book-to-market ratio—exert a statistically significant positive influence on the excess returns of state-owned company stocks in the year 2021